PENYELESAIAN SENGKETA KONSUMEN BERBASIS KEARIFAN LOKAL: PELUANG DAN TANTANGAN - Suwandono, Agus (Jurnal Panorama Hukum, 2018)
One of the functions of traditional institutions is to maintain the balance of the order and harmony of indigenous peoples. This research discusses the existence and the possibility of applying consumer dispute settlement based on local wisdom. The research method used empirical juridical supported using primary data secondary data. The results showed that the existence of traditional institutions in resolving the dispute depends on the obedience and submission of indigenous peoples would be customary law and traditional institutions. The implementation of consumer dispute settlement possible based on local wisdom applied with due regard to regional characteristics, customs and laws. Keywords: consumer, local wisdom, settlement of disputes.